Methicillin and inducible clindamycin resistance in clinical Staphylococcus aureus isolates: a cross-sectional study from Northwest Ethiopia - Zemen Addis; Zemen Addis; Yibeltal Aschale; Abebe Fenta; Zigale Hibstu Teffera; Abateneh Melkamu; Abeba Tigab; Tebelay Dilnessa (Frontiers in Microbiology)
BackgroundStaphylococcus aureus is a major pathogenic bacterium associated with high morbidity and mortality worldwide. It exhibits resistance to multiple antibiotics, complicating treatment options. Despite its clinical significance, there is limited data on the prevalence of S. aureus infections and the patterns of methicillin and inducible clindamycin resistance, particularly in Ethiopia. Understanding these resistance trends is essential for guiding appropriate therapy and improving patient outcomes.ObjectiveTo assess the prevalence of S. aureus, methicillin and inducible clindamycin resistance patterns, and associated factors among patients with suspected bacterial infection at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia.MethodA hospital-based cross-sectional study was conducted among patients suspected of bacterial infections from 10 June 2023 to 28 February 2024. Blood, wound swab, cerebrospinal fluid, urine, eye swab, synovial fluid, ear swab, and pleural fluid were collected aseptically and inoculated onto appropriate media. S. aureus was identified based on colony morphology, Gram staining, DNase test and biochemical tests. Antimicrobial susceptibility testing was performed on the isolates using the disk diffusion and the D-test techniques based on CLSI guideline. Data were entered into SPSS version 26 for analysis. Logistic regression was applied to assess the relationship between predictors and the outcome variable. A P-value of ≤ 0.05 with a 95% CI was considered statistically significant.ResultsAmong the 339 study participants, 38 (11.2%) (95% CI: 8–15) tested positive for S. aureus. Of these isolates, 14/38 (36.9%) were resistant to methicillin, 5/38 (13.1%) isolates were resistance to clindamycin by routine disk diffusion test whereas 10/38 (26.3%) isolates exhibited inducible clindamycin resistance using the D-test. The level of multidrug resistance was noted in 10/38 (26.3%) of the isolates. Significant factors associated with S. aureus infection included illiteracy (AOR = 13.51; 95% CI: 3.56–21.90; P = 0.018), having larger family size (AOR = 12.14; 95% CI: 2.38–20.43; P = 0.024), and income level of less than 3,000 ETB (AOR = 6.20; 95% CI: 1.03–30.09; P = 0.046).ConclusionThe study revealed an 11.2% occurrence of S. aureus among the study participants, with a substantial proportion exhibiting methicillin resistance (36.9%) and inducible clindamycin resistance (26.3%). These findings highlight a higher burden of clindamycin resistance in MRSA, underscoring the need for routine D-test screening to guide appropriate antibiotic therapy. Additionally, factors such illiteracy, low income and residing in rural areas were associated with S. aureus infection. Targeted health education initiatives should be implemented, especially in rural areas and among populations with low literacy levels, to improve hygiene practices and reduce transmission.